A leitura de conto de Jorge Machado na formação de leitores no contexto de sala de aula - FERREIRA, Lucileia Lobato (2023)
This work deals with the importance of reading the short story in the formation of each individual, a literature that, being a short story, is not intended for a single public. I prioritize in this work the Abaetetubense short story literature of the writer Jorge Machado who has not received the importance deserved by the people Abaetetubense. A reading of a short story by Jorge Machado― in this work by completion of the course makes us “value” our culture that has been set aside by our people. The issue of work with reading has generated discourses in the field of diverse education, proposals seek adapt school work to better ways of teaching and learning, the short stories as a resource of this writer as a reading strategy improves the form of the teacher to teach classes, provoking a growing interaction between the student and the tales. The present work is based on the question of the tale of Jorge Machado as a reading strategy to encourage students to have the I inhabit reading, the true role of the teacher as a mediator of knowledge in the teaching-learning process is to present a methodology capable of arousing the student's interest in a literature enjoyable and easy to understand.